The Effect of Extra Virgin Olive Oil (EVOO) on Expression of Vascular Endhothelial Growth Factor (VEGF) and Arteriole Number on Endometrium of Female Rattus norvegicus of Wistar Strain Exposed to Rhodamin B - Siti Anisak; Hidayat Sujuti; Sutrisno Sutrisno; Karyono Mintaroem; Tatit Nurseta; Umi Kalsum (Health Notions, 2018)
Rhodamin B is dangerous for body due to its ability to improve oxidative stress on various reproduction tissues on female. However, there is no significant scientific proof that Rhodamin B exposure influences VEGF and the number of arteriole on endometrium. VEGF and arteriole is crucial to angiogenesis process of endometrium. This study aimed at finding out the effect of EVOO on Expression of VEGF and Arteriole number of female Rattus Norvegicus of Wistar Strain exposed to Rhodamin B.Keywords: Rhodamin B, Extra Virgin Olive Oil (EVOO), Vascular Endothelial Growth Factor (VEGF), Arteriole